Compensatory and Adaptive Features of the Cerebellum under Stress - Alexey Rozhentsev (Journal of Global Pharma Technology, 2016)
The paper discusses the results of the study of compensatory and adaptive changes in rat cerebellar tissues under stress. As a stress factor, the experiment simulated (hypobaric) hypoxia. Since hypoxia remains one of the central issues in the modern medical science, it is directly or indirectly related to human diseases of various etiologies. To identify the features of compensatory and adaptive changes in the rat cerebellum under the action of hypoxia, we conducted comprehensive histological and histochemical studies. At the early stages of hypoxia, changes in the cerebellar tissue could be found, that were characterized by a significant increase in the volume of intracellular structures. With a prolonged hypoxia, a decrease in the volume of intracellular structures was observed which, in turn, entailed a decrease in total glycosaminoglycans and a change in the ratio of sulfated and non-sulfated glycosaminoglycans. In addition, we noted cerebellar neuron migration into the molecular layer. The experiment revealed that hypoxia has a significant effect on the intensity of metabolic processes in cells, with the generation of intermediate metabolic products leading to a change in pH.Keywords: Hypoxia, Cerebellum, Rats, Compensatory and adaptive changes, Glycosaminoglycans.